Restructuring the Labour Market - Ashton, D. author. aut Link
XI, 230 p.
Keywords: This book represents an advance in our knowledge of the labour market. For the first time it combines the analysis of both quantitative and qualitative data to produce an explanation of the main changes which have transformed the labour market during the recession. For the first time it demonstrates the segmented character of the youth labour market and the significance of the local labour markets. The result is a substantial contribution to labour market segmentation theory and to the analysis of social policy in this field.